Dynamic Susceptibility Contrast Perfusion Magnetic Resonance Imaging Demonstrates Reduced Periventricular Cerebral Blood Flow in Dogs with Ventriculomegaly - Schmidt, Martin J.; Kolecka, Malgorzata; Kirberger, Robert; Hartmann, Antje (Frontiers in Veterinary Science, 2017)
The nature of ventriculomegaly in dogs is still a matter of debate. Signs of increased intraventricular pressure and atrophy of the cerebral white matter have been found in dogs with ventriculomegaly, which would imply increased intraventricular pressure and therefore a pathological condition, i.e to some extent. Reduced periventricular blood flow was found in people with high elevated intraventricular pressure. The aim of this study was to compare periventricular brain perfusion in dogs with and without ventriculomegaly using perfusion weighted-magnetic-resonance-imaging to clearify as to whether ventriculomegaly might be associated with an increase in intraventricular pressure. Perfusion was measured in 32 Cavalier King Charles spaniels with ventriculomegaly, 10 CKCSs were examined as a control group. Cerebral blood flow (CBF) was measured using free-hand regions of interest (ROI) in five brain regions: periventricular white matter, caudate nucleus, parietal cortex, hippocampus and thalamus. CBF was significantly lower in the periventricular white matter of the dogs with ventriculomegaly (p=0.0029) but not in the other ROIs. Reduction of periventricular CBF might imply increase of intraventricular pressure in ventriculomegaly.